2003
DOI: 10.1207/s15327906mbr3804_4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and Treatment of Missing Item Scores in Test and Questionnaire Data

Abstract: This article first discusses a statistical test for investigating whether or not the pattern of missing scores in a respondent-by-item data matrix is random. Since this is an asymptotic test, we investigate whether it is useful in small but realistic sample sizes. Then, we discuss two known simple imputation methods, person mean (PM) and two-way (TW) imputation, and we propose two new imputation methods, response-function (RF) and mean response-function (MRF) imputation. These methods are based on few assumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
159
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(166 citation statements)
references
References 18 publications
4
159
1
2
Order By: Relevance
“…Deterministic methods, however, assume that all conditions leading to missing item scores are perfectly known, an assertion that may not be entirely valid. Sijtsma and van der Ark (2003) discussed some simple methods and proposed two nonparametric single-imputation methods, one of which seemed to be superior in recovering several statistical properties of the original complete data from an incomplete data set. In addition, van Ginkel, van der Ark, and Sijtsma (2007) showed that multiple-imputation versions of some methods discussed by Sijtsma and van der Ark produced small discrepancies when compared to the statistical properties of the completely observed data.…”
Section: Missing-data Mechanismsmentioning
confidence: 99%
“…Deterministic methods, however, assume that all conditions leading to missing item scores are perfectly known, an assertion that may not be entirely valid. Sijtsma and van der Ark (2003) discussed some simple methods and proposed two nonparametric single-imputation methods, one of which seemed to be superior in recovering several statistical properties of the original complete data from an incomplete data set. In addition, van Ginkel, van der Ark, and Sijtsma (2007) showed that multiple-imputation versions of some methods discussed by Sijtsma and van der Ark produced small discrepancies when compared to the statistical properties of the completely observed data.…”
Section: Missing-data Mechanismsmentioning
confidence: 99%
“…The RF imputation method was first proposed by Sijtsma and Van der Ark [2] for data related to test or scale. In the Rasch model, for a patient with a latent trait level, the probability of having a score x on item j is called the item response function, shown as, P(Xj=x|θ).…”
Section: Imputation Methodsmentioning
confidence: 99%
“…The RF imputation uses the estimated item response function to impute item scores, and it has been proven to be an efficient imputation method for unidimensional scales in simulation studies. [2][3][4] The classical test theory and item response theory…”
Section: Imputation Methodsmentioning
confidence: 99%
See 2 more Smart Citations